2016
DOI: 10.3389/fpls.2016.00417
|View full text |Cite
|
Sign up to set email alerts
|

Overview of OVATE FAMILY PROTEINS, A Novel Class of Plant-Specific Growth Regulators

Abstract: OVATE FAMILY PROTEINS (OFPs) are a class of proteins with a conserved OVATE domain. OVATE protein was first identified in tomato as a key regulator of fruit shape. OFPs are plant-specific proteins that are widely distributed in the plant kingdom including mosses and lycophytes. Transcriptional activity analysis of Arabidopsis OFPs (AtOFPs) in protoplasts suggests that they act as transcription repressors. Functional characterization of OFPs from different plant species including Arabidopsis, rice, tomato, pepp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 50 publications
0
60
0
Order By: Relevance
“…For example in melon, some QTLs associated to fruit shape colocalize with members of the OVATE family proteins (OFP). Genes of this family are also involved in tomato fruit morphology [6668]. The anchorage of the RIL map to the genome sequence provide the list of genes annotated in the IFSh_3, IFLe_3, IFWi_3, MFSh_3, MFLe_3 and MFWi_3 region (Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…For example in melon, some QTLs associated to fruit shape colocalize with members of the OVATE family proteins (OFP). Genes of this family are also involved in tomato fruit morphology [6668]. The anchorage of the RIL map to the genome sequence provide the list of genes annotated in the IFSh_3, IFLe_3, IFWi_3, MFSh_3, MFLe_3 and MFWi_3 region (Additional file 6).…”
Section: Resultsmentioning
confidence: 99%
“…In the DET-Arid set of roots, we detected an enrichment of puta- (Wang, Chang, & Ellis, 2016;Wang, Chang, Guo, & Chen, 2007) 1 and 2 Ag_38780 AT2G24395, chaperone protein dnaJ-related PWQ (8.31e−05) Regulation of the activity of Hsp70 chaperones (Walsh, Bursać, Law, Cyr, & Lithgow, 2004) and protein protection against stress-induced denaturation (Frydman, 2001) 2 Ag_12760 AT3G54810, GATA8, Plant-specific GATAtype zinc finger transcription factor family protein PWQ (0.00363); PDM (0.01916) Associated with the control of plant growth and development (Manfield, Devlin, Jen, Westhead, & Gilmartin, 2006) 2 Ag_135 AT1G28440, HSL1, HAESA-like 1 PWQ (9.09e−05) The Ag_135 transcript has a kinase domain and is associated with growth and abiotic stress signalling (ten Hove et al, 2011) 2 Ag_15249 AT2G34790, MEE23, FAD-binding Berberine family protein PWQ (8.31e−05) Involved in the lignification of the cell wall; mediates the oxidation of monolignols (Daniel et al, 2015) and is required for endosperm development (Pagnussat et al, 2005) 2 Ag_10980 AT5G13530, KEG, keep on going PWQ (0.00041); PDM (0.02034) Associated with the control of plant growth and development and critical for seedling regulation of abscisic acid perception and signalling (Stone, Williams, Farmer, Vierstra, & Callis, 2006) 2 Ag_26982 AT3G01640, GLCAK, glucuronokinase G PWQ (0.00011) Involved in the biosynthesis of UDP-glucuronic acid, providing nucleotide sugars for the polymerization of cell-wall compounds (Pieslinger, Hoepflinger, & Tenhaken, 2010) 2 Ag_11269 AT2G25730, unknown protein PWQ (0.00016) The Ag_11269 transcript has a TPR 2 domain and, thus, may be involved in thylakoid membrane biogenesis and with the photosynthetic machinery stabilization and repair (Bohne et al, 2016) 2 Ag_43282 AT1G04300, MUSE13, TRAF-like superfamily protein PWQ (8.31e−05) MUSE13 regulates the turnover of nucleotide-binding domain and leucine-rich repeatcontaining immune receptors. Loss of MUSE13 and MUSE14 leads to enhanced pathogen resistance, NLR ...…”
Section: Photorespirationmentioning
confidence: 97%
“…PWQ (8.31e−05) Associated with thylakoid membrane biogenesis and chloroplast protein synthesis and essential for early embryogenesis in response to light stimulus (Bang et al, 2009) 1 and 2 Ag_29619 AT2G18500, OFP7, ovate family protein 7 PWQ (0.00019) May be involved in various aspects of plant growth and participate in suppressing cell elongation (Wang, Chang, & Ellis, 2016;Wang, Chang, Guo, & Chen, 2007) 1 and 2 Ag_38780 AT2G24395, chaperone protein dnaJ-related PWQ (8.31e−05) Regulation of the activity of Hsp70 chaperones (Walsh, Bursać, Law, Cyr, & Lithgow, 2004) and protein protection against stress-induced denaturation (Frydman, 2001) 2 Ag_12760 AT3G54810, GATA8, Plant-specific GATAtype zinc finger transcription factor family protein PWQ (0.00363); PDM (0.01916) Associated with the control of plant growth and development (Manfield, Devlin, Jen, Westhead, & Gilmartin, 2006) 2 Ag_135 AT1G28440, HSL1, HAESA-like 1 PWQ (9.09e−05) The Ag_135 transcript has a kinase domain and is associated with growth and abiotic stress signalling (ten Hove et al, 2011) 2 Ag_15249 AT2G34790, MEE23, FAD-binding Berberine family protein PWQ (8.31e−05) Involved in the lignification of the cell wall; mediates the oxidation of monolignols (Daniel et al, 2015) and is required for endosperm development (Pagnussat et al, 2005) 2 (FDR), false discovery rate values (Benjamini-Hochberg procedure) for genetic-environment association tests; NA, genetic-environment association tests were not available for data set (1) due to unavailability of environmental data for the PA-arid sites in public databases; PWQ: precipitation of the warmest quarter; PDM: precipitation of the driest month; PANNUAL: Annual precipitation; SSS: PWQ (8.31e−05) Associated with thylakoid membrane biogenesis and chloroplast protein synthesis and essential for early embryogenesis in response to light stimulus (Bang et al, 2009) 1 and 2 Ag_29619 AT2G18500, OFP7, ovate family protein 7 PWQ (0.00019) May be involved in various aspects of plant growth and participate in suppressing cell elongation (Wang, Chang, & Ellis, 2016;…”
Section: Photorespirationmentioning
confidence: 99%
“…This suggests that VDD and female gametogenesis may be regulated by other factors rather than STK complexes during dormancy in Prunus spp. Another jojoba acyl CoA reductaserelated male sterility protein (Prupe.6G126800) involved in flower wax biosynthesis (Busta and Jetter, 2017) and ovate family protein 2 (OFP2, Prupe.6G290900) involved in vascular formation (Schmitz et al, 2015;Wang et al, 2016) were also downregulated during ecodormancy, indicating that some floral development activities may be completed prior to entering ecodormancy. Julian et al (2011) reported a rapid development of stamen and vascular differentiation upon CR fulfillment in apricot (Julian et al, 2011).…”
Section: Flower Development-related Genes Have Specific Patterns Of Ementioning
confidence: 99%